2019
DOI: 10.1101/562827
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transient perturbation of the left temporal cortex evokes plasticity-related reconfiguration of the lexical network

Abstract: While much progress has been made in how brain organization supports language function, the language network's ability to adapt to immediate disturbances by means of reorganization remains unclear. The aim of this study was to examine acute reorganizational changes in brain activity related to conceptual and lexical retrieval in unimpaired language production following transient disruption of the left middle temporal gyrus (MTG). In a randomized single‐blind within‐subject experiment, we recorded the electroen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
(65 reference statements)
1
1
0
Order By: Relevance
“…Therefore, healthy participants were tested with MEG while performing a context‐driven picture‐naming task, similar to sentence completion (Wilson et al., 2017). Replicating previous findings (Klaus et al., 2020; Piai et al, 2014, 2015, 2017, 2018, 2020) in both sessions, the behavioral differences demonstrated faster picture naming for constrained than unconstrained sentences, indicating that the context of constrained sentences provides the necessary information for enabling conceptual and lexical retrieval already prior to the target picture being shown. Also the MEG source level results were in accordance with these findings and revealed the expected power decreases in the alpha–beta frequency range in the left hemisphere.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Therefore, healthy participants were tested with MEG while performing a context‐driven picture‐naming task, similar to sentence completion (Wilson et al., 2017). Replicating previous findings (Klaus et al., 2020; Piai et al, 2014, 2015, 2017, 2018, 2020) in both sessions, the behavioral differences demonstrated faster picture naming for constrained than unconstrained sentences, indicating that the context of constrained sentences provides the necessary information for enabling conceptual and lexical retrieval already prior to the target picture being shown. Also the MEG source level results were in accordance with these findings and revealed the expected power decreases in the alpha–beta frequency range in the left hemisphere.…”
Section: Discussionsupporting
confidence: 86%
“…We used the same sentence completion as picture‐naming paradigm (i.e., context‐driven picture naming) as previously employed in electrophysiological studies by our group (Klaus, Schutter, & Piai, 2020; Piai, Klaus, & Rossetto, 2020; Piai et al, 2017; Piai, Roelofs, & Maris, 2014; Piai, Roelofs, Rommers, & Maris, 2015; Piai, Rommers, & Knight, 2018). This paradigm has repeatedly elicited robust oscillatory power decreases in the alpha–beta range (8–25 Hz) prior to picture onset in healthy participants as well as stroke patients.…”
Section: Introductionmentioning
confidence: 99%